2011
DOI: 10.1007/s00405-011-1812-7
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological and electrophysiological testing of olfactory and gustatory function in patients with multiple sclerosis

Abstract: The olfactory (OF) and gustatory function in multiple sclerosis (MS) patients and possible influencing variables of the disease, such as depression or fatigue, were determined. In an open prospective controlled clinical study 30 patients with MS and 30 healthy controls matched for age, sex and smoking-habits were investigated. With Mini Mental State Examination cognitive dysfunction was excluded, with Expanded Disability Status Scale the patient's ability to accomplish the tests was ensured. The severity of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 22 publications
1
21
1
Order By: Relevance
“…The extent of OEP disturbance in MS related to poor performance on the UPSIT score and to the extent of physical disability, as measured by Expanded Disability Status Score (EDSS), in the disease (see clinical association section below) 22 38. Other independent groups have corroborated these OEP findings in MS, adding further credence to physiological disturbance of these olfactory structures at some point in the clinical evolution of the disease 29 31 39…”
Section: Olfactory Dysfunction In Cns Demyelinating Diseasesmentioning
confidence: 91%
See 2 more Smart Citations
“…The extent of OEP disturbance in MS related to poor performance on the UPSIT score and to the extent of physical disability, as measured by Expanded Disability Status Score (EDSS), in the disease (see clinical association section below) 22 38. Other independent groups have corroborated these OEP findings in MS, adding further credence to physiological disturbance of these olfactory structures at some point in the clinical evolution of the disease 29 31 39…”
Section: Olfactory Dysfunction In Cns Demyelinating Diseasesmentioning
confidence: 91%
“…OEPs are deranged in MS 22 29 31 38 39. In a cohort of 45 patients with MS and 47 controls, Hawkes et al found an increase in latency and a decrease in amplitude of the H 2 S (olfactory)-related OEP in MS compared with controls, suggesting demyelination and axonal loss within olfactory bulb/tract and/or olfactory brain as an element of MS pathology 22 38.…”
Section: Olfactory Dysfunction In Cns Demyelinating Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies evaluating the relationship between MS and the three olfactory abilities used psychophysical tests [11], [17], [19][23], such as the Sniffin' Sticks Test [24], [25] and the University of Pennsylvania Smell Identification Test (UPSIT) [26]. However, the psychophysical tests of identification and discrimination require complex cognitive functions and high attention levels which could be compromised also in the early stage of MS [27], [28].…”
Section: Introductionmentioning
confidence: 99%
“…Odors binding to the olfactory receptor neurons trigger olfactory activity [8]. The processing of odors within the central nervous system includes the orbitofrontal cortex, the limbic system, insula and cerebellum, among other structures [9,10]. Gustatory fibers, on the other hand, reach the brain via the facial, glossopharyngeal, and vagal nerves.…”
Section: Introductionmentioning
confidence: 99%